Interfacial microstructure evolution and mechanical properties of AlCoCrFeNi2.1 alloy by multilayer additive hot compression bonding. (May 2023) - Zhang, Yubo; Ding, Chenghao; Liu, Jiajing; Lu, Yiping; Li, Tingju
Abstract: Multilayer additive hot-compression bonding (MAHCB) is an efficient manufacturing method for obtaining a large alloy with a uniform composition and microstructure. In this work, the method was applied to an AlCoCrFeNi2.1 eutectic alloy for the first time. The results show that the bonding temperature significantly affects the interface microstructure, improving dynamic recrystallization (DRX) and interface grain boundary migration (GBM), as well as reducing defects at the interface. Optimal bonding was obtained at a bonding temperature of 1250 °C. The interfacial Vickers hardness reaches 317 HV, and the tensile‒shear strength reaches 894 MPa, which are 9.3% and 16.5% improved, respectively, compared with the as-cast sample. The interface microstructure and fracture morphology are very close to those of the as-cast state. The combination of temperature and strain promote the interfacial bonding process, which mainly include DRX in the FCC phases, element diffusion between the FCC and B2 phases, and transformation of harmful B2–B2 interfaces into those of FCC-B2 type. Highlights: The MAHCB process was used to build a larger AlCoCrFeNi2.1 EHEA ingot in this study. The microstructure scarcely changed after successful MAHCB, very close to the as-cast condition. The interfacial Vickers hardness and the tensile‒shear strength are even 9.3% and 16.5% improved, respectively, compared with the as-cast sample.